2021
DOI: 10.2147/opth.s293695
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Epithelial Thickness Profile in Healthy Portuguese Children by High-Definition Optical Coherence Tomography

Abstract: Introduction and Objective To evaluate corneal epithelial thickness (ET) and corneal thickness (CT) profiles in healthy eyes of Portuguese children and provide information to establish the first normative Caucasian database for these age group. Methods Sixty healthy eyes of 60 children aged between 8 and 18 were evaluated using the Cirrus high-definition optical coherence tomography device. The average ET and CT were assessed using Cirrus Review Software with predefined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 47 publications
3
17
0
Order By: Relevance
“…Mean epithelial thickness was signi cantly higher in male than female in all three zones (central, paracentral, and peripheral, p < 0.05, all). This is consistent with previous studies (4,5,17,28). It has been postulated that males have thicker CET than females because the total corneal thickness was reported to be thicker in males than in females (29,30).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Mean epithelial thickness was signi cantly higher in male than female in all three zones (central, paracentral, and peripheral, p < 0.05, all). This is consistent with previous studies (4,5,17,28). It has been postulated that males have thicker CET than females because the total corneal thickness was reported to be thicker in males than in females (29,30).…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with previous data (3,4,5,13,14,17,25,26), our ndings demonstrated that the corneal epithelium was nonuniform. The superior epithelium was thinner than the inferior one.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To the authors' knowledge, there are a few studies using this OCT device in healthy adults and children, and our current study is the first for KC detection. [26][27][28] However, it has been shown in studies conducted with different OCT devices that these parameters differ significantly in KC eyes compared with healthy ones. 10,11,[14][15][16]18,29 Pachymetric minimum and min-med indicates focal thinning in the cornea; pachymetric SN-IT detects asymmetric thinning; and epithelial SN-IT measures asymmetric thinning of the corneal epithelium.…”
Section: Discussionmentioning
confidence: 99%